Determinación de los agentes patógenos causales de la pata negra en ajonjolí (Sesamum indicum L.) - Rojas Mairena, K.M.; López Arguello, C. Asesor; Gutiérrez Barrera, Y. Asesor; Padilla, D. Asesor; Monterroso Salvatierra, D. Asesor (Managua (Nicaragua), 2000)
Sumario (Es)
Ilus.; 21 ref.
Tesis (Ing Agr)
Keywords: SESAMUM INDICUM; ORGANISMOS PATOGENOS; PATOGENICIDAD; ENFERMEDADES DE LAS PLANTAS; INOCULACION; INVERNADEROS; NICARAGUA